Identification of Mucormycosis in post Covid-19 case using Deep CNN - RangaSwamy Sirisati, C. Srinivasa Kumar, A. Gauthami Latha, B. Narendra Kumar, KanusuSrinivasa Rao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Patients infected by coronavirus disease 2019, particularly in India, are more likely to develop rhino-orbital mucormycosis, which has risen in frequency. Diabetes mellitus (DM) is a renowned chance element during COVID-19 infection and mucormycosis (fungal infection of the gut) (fungal infection). This research aims to conduct a methodical review of the paper to ascertain the characteristics of people who have mucormycosis and COVID-19. We conducted a keyword search of the electronic dataset database from its inception until June 2021, and the findings are presented in the following report. This work compiled all of the fine-grained information from case history records of patients with COVID-19 and mucormycosis worldwide. We next examined the patient steroid usage, health characteristics, mucormycosis location, associated comorbidities, and prognosis of COVID-19 patients, among other things. Many cases of mucormycosis are recorded in people who have been infected with COVID-19, with an additional few other cases reported from other parts of the globe. Most instances (82 percent) occurred in India, with Mucormycosis being found in the vast majority of males (80 percent) and about 40 percent of COVID-19 patients who were active and recovered. Patients with pre-existing diabetes were found to have DM in above 80 percent of patients. The DKA (Diabetic ketoacidosis) was found in 15 percent of patients with pre-existing diabetes. Corticosteroids were utilized to treat COVID-19 in 76.3 percent of individuals studied. Mucormycosis of the nose and sinuses was the most prevalent kind (88.9 percent), followed by rhino-orbital mucormycosis (14 percent ). (56.7% ). In 30.7 percent of the instances, there was a death to record. Diabetes, prolonged corticosteroid usage, and the presence of COVID-19 all appear to be associated with an increase in mucormycosis. Every effort should be made to maintain optimum glucose levels in COVID-19 patients, with corticosteroids used sparingly.